A gendered profession the question of representation in space making - Brown, James Benedict (RIBA Publishing, 2016)
"The issue of gender inequality in architecture has been part of the profession's discourse for many years, yet the continuing gender imbalance in architectural education and practice remains a difficult subject. This book seeks to change that. It provides the first ever attempt to move the debate about gender in architecture beyond the tradition of gender-segregated diagnostic or critical discourse on the debate towards something more propositional, actionable and transformative. To do this, A Gendered Profession brings together a comprehensive array of essays from a wide variety of experts in architectural education and practice, touching on issues such as LGBT, age, family status, and gender-biased awards."--Cover